Pengembangan Perangkat Pembelajaran Tematik dengan Model Pembelajaran Kooperatif Tipe Talking Stick untuk Siswa Kelas II SD - Amaliya Sidikiyah; Siti Maghfirotun Amin; Nafiah Nafiah; Sri Hartatik (FKIP, Universitas Palangka Raya, 2024)
This study aims to describe the validity, practicality, and effectiveness of the thematic learning tools of the talking stick type cooperative learning model for second grade students in elementary school. This research is based on the Borg and Gall development model, involving 5 main steps: Conduct product analysis to be developed; Develop initial product; Expert validation and revision; Smallscale field trials and product revisions; Large-scale field trials and final products. The instruments used in this study were lesson plans assessment questionnaires, teaching materials assessment questionnaires, LKPD assessment questionnaires and assessment instrument assessment questionnaires to measure validity, learning observation sheets and student response questionnaires to measure practicality, as well as learning achievement tests to measure the effectiveness of learning tools. The validity quality of learning devices that meet the valid criteria is shown by the average total validity of lesson plans, namely 3.48, the average total validity of teaching materials, namely 3.46, the average total validity of LKPD, which is 3.54, and the average total validity of assessment instruments 3.53. The practical quality of learning tools that meet practical criteria is shown by the average total student response questionnaire of 3.06 and the average total observation sheet of 3.54. The quality of the effectiveness of learning tools in terms of the results of student learning tests meets the effective criteria of achieving 100% completeness.